STUDI KEMAMPUAN MEMBUAT MIND MAP BERBASIS PEMAHAMAN ARTIKEL THE JAKARTA POST PADA MATA KULIAH EXTENSIVE READING - Pudiyono Pudiyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
The aims of the research were to find out (a) the level of the students’ ability in making mind map based on the article of The Jakarta Post in Extensive Reading, (b) the problems the students have in comprehending the article of The Jakarta Post in Extensive Reading in making mind map. The data collecting technique used was a test of reading based on comprehension. The population of the research was all students of semester 6 totaling to 161 students. While the sample was taken from all 4 classes by which each class was taken at about 25%. Therefore the total sample was 48 students. The result of data analysis showed that the average ability of the students reached only 59.02. In detail, research result showed that none of the samples (0 %) could do the mind map correctly or get an A. The participants who got good achievement (B) amounted to only 4 people (2.48%). The majority of the participants belonged to the level of good enough to be able to make main idea analysis in order to make the mind map. The not good enough level became the majority achievement among all amounting to 89.43%. The students’ ability which got the perfect inability level in making the mind map rose to 8.09%. The problems the students had in making the mind map was the fact that they had no idea in identifying main ideas of the content of the text. Besides that students also failed in comprehending the new vocabulary they found while they were reading the articles. Failure in comprehending the new difficult words led the to get the failure in identifying main ideas by which in turns they found themselves to have no clear map of their understanding of the articles they had read. Key word: comprehension, mind mapping, new vocabulary, authentic text, natural